Malvinas War Poetry : a Comparative Approach to Gustavo Caso Rosendi’s Soldados and Tony McNally’s Screaming in Silence from the Perspective of Trauma Studies - Lau, Ignacio (2019)
Maestría en Inglés con orientación angloamericana